Stastical Testing of Cancer Patients in J&K and Rajasthan with Punjab: Investigating the Relationship between Water Impurities and Cancer Incidence in J&K, Rajasthan, and Punjab (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Objective of study is to examine the cause of cancer prone to water impurities, pesticides and fertilizers by studying the data provided by the authorities and the Mathematical Modelling and a connotation of testing through the Hypothetical Testing. MAX SUPER SPECIALITY HOSPITAL, BATHINDA is a unit of Hometrail Buildtech Pvt. Ltd. It is a Cancer and Cardiac hospital in Bathinda. A study on Max super speciality hospital, Bathinda (Punjab) about cancer patients may be based on drinking water’s impurities and upshot of fertilizers. The graph representation and connotation of student’s t-test for comparative study between Punjab and H.P., Haryana Rajasthan are based on the data given by the authorities of the max super speciality hospital, bathinda. We want s study to know the number of cancer patients in the above mentioned hospital is more as compared to other hospital. As the hospital is situated in Punjab, the momentous number of cancer patients of Punjab is more in comparison to other state patients. In this study of Mathematical modelling gives the reason of cancer.So the study about the max super speciality hospital, bathinda is very momentous to help the study of cancer patient’s nature prone to impure water and the measures of the quantities are grown day by day in this region.